Fauna and microbial attributes of an Ultisol under cover crop systems in the South of Brazil - Almeida, Denice Oliveira; Bayer, Cimélio; Almeida, Henrique Cesar (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate, in a long-term experiment, the fauna and microbiological attributes of an Ultisol under no-tillage cover crop. The study was carried out in Eldorado do Sul, RS, Brazil, after 27 years of implantation of an experiment evaluating the following crop systems: O/C, oat/corn; V/C, vetch/corn; OV/C, oat + vetch/corn; OV/CP, oat + vetch/corn + cowpea; and L/M, lablab/corn. A randomized complete block design was used, with three replicates. Samplings of fauna, performed with pitfalls, and of microbiological attributes were done after cover crop management, in spring; during corn crop cycle, in summer; after corn crop harvest, in autumn; and during cover crop cycle, in winter. The inclusion of legume intercropped or in succession to cover crops promoted the occurrence of edaphic fauna and increased microbial biomass C and N, which favored cycling potential and nutrient availability. The O/C cover crop system with grasses favored the Diptera, Hemiptera, and Diplopoda orders. Overall, the best cover crop systems under notillage are those with legume inclusion.
Keywords: bioindicators; microbial biomass; cover crop intercropping; edaphic organisms; no-tillage; soil quality.